THE ROLE OF ACCOUNTING INFORMATION IN THE IMPLEMENTATION OF CORPORATE POLICY OF THE BUSINESS ENTITY IN THE FIELD OF ECOLOGY OF NATURE - O. Kovalenko (Вестник университета, 2016)
The article describes the main approaches to the definition of the role of accounting information in the implementation of corporate policy of the business entity in the field of ecology of nature management, the analysis of the doctrinal principles of the state policy in the sphere of ecology, methods of cost accounting, reporting. The author gives suggestions for the method of forming integrated reporting that combines financial information, social content, the results of monitoring of the state of the natural environment, the grouping of investments in environmental activities for the criterion of utility.